Establishment and evaluation of an indirect ELISA for detection of antibodies to goat Klebsiella pneumonia - Ruichang Chen; Hongqi Shang; Xiangyun Niu; Jin Huang; Yongqiang Miao; Zhou Sha; Liting Qin; He Huang; Duo Peng; Ruiliang Zhu (BMC Veterinary Research, 2021)
Abstract Background Klebsiella pneumonia, a Gram-negative bacterium belonging to the genus Enterobacter, causes many human and livestock diseases. Notably, infected goats may develop pneumonia, septicemia, which can lead to occasional death, resulting in great economic losses in goat-farming industry. However, there are little systematic methods for detection of goat Klebsiella pneumoniae in livestock production. Results In this study, we developed a Klebsiella pneumoniae goat polyclonal antibody and established an indirect ELISA method to detect the Klebsiella pneumoniae. After screening and optimizing the conditions for detection, we determined the optimal working dilutions of the coated-bacterial antigen, the polyclonal antibody, and the enzyme-labeled secondary antibody that were 1:800 (2.99 × 107 CFU/ml), 1:6400, and 1:5000, respectively. The optimal condition of coating and blocking were both 4 °C for 12 h. The optimal dilution buffers of bacterial antigen, the antibodies, and the blocking buffer were 0.05 mol/L carbonate buffer, 1% BSA phosphate buffer, and 1.5% BSA carbonate buffer, respectively. The cut-off value was determined to be 0.28, and the analytical sensitivity was 1:800 (dilution of a positive sample). Furthermore, there was no cross-reaction between the coated antigen and goat serum positive for antibodies against other bacteria, indicating that indirect ELISA could detect Klebsiella pneumoniae specifically in most cases. The average coefficients of variation of intra-assay and inter-assay were 4.37 and 5.17% indicating favorable reproducibility of indirect ELISA. In the detection of clinical veterinary samples, the positive rate of indirect ELISA was 6.74%, higher than that of conventional agglutination assays. Conclusions Taken together, we successfully established an indirect ELISA method for detecting antibodies against Klebsiella pneumoniae in goats, which can be applied in production.